Pointwise Approximation of Functions from 𝐿𝑝(𝑤)𝛽 by Linear Operators of Their Fourier Series - Włodzimierz Łenski; Bogdan Szal (Journal of Function Spaces and Applications)
We show the results, corresponding to theorem of Lal (2009), on the rate of pointwise approximation of functions from the pointwise integral Lipschitz classes by matrix summability means of their Fourier series as well as the theorems on norm approximations.